Enzymatic reduction of acetophenone derivatives with a benzil reductase from Pichia glucozyma (KRED1-Pglu): electronic and steric effects on activity and enantioselectivity. Issue 13 (8th March 2016) - Contente, Martina L.; Serra, Immacolata; Palazzolo, Luca; Parravicini, Chiara; Gianazza, Elisabetta; Eberini, Ivano; Pinto, Andrea; Guidi, Benedetta; Molinari, Francesco; Romano, Diego
Abstract : Enantioselective reduction of mono-substituted acetophenones by ketoreductase KRED1-Pglu. Abstract : A recombinant ketoreductase from Pichia glucozyma (KRED1-Pglu) was used for the enantioselective reduction of various mono-substituted acetophenones. Reaction rates of meta - and para -derivatives were consistent with the electronic effects described by σ -Hammett coefficients; on the other hand, enantioselectivity was determined by an opposite orientation of the substrate in the binding pocket. Reduction of ortho -derivatives occurred only with substrates bearing substituents with low steric impact ( i.e., F and CN). Reactivity was controlled by stereoelectronic features (CO length and charge, shape of LUMO frontier molecular orbitals), which can be theoretically calculated.